(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The Unitary State of the Republic of Indonesia faces complex challenges in realizing justice and welfare for all people spread across vast territories with diverse ethnicities, cultures, and geographical conditions. To address these challenges, following the 1998 reform era, Indonesia implemented asymmetric decentralization policies through granting special autonomy status to several regions such as Aceh, Papua, and the Special Region of Yogyakarta based on their respective historical, cultural, and socio-political specificities. This research aims to analyze the implementation of special autonomy as a manifestation of asymmetric decentralization within the framework of Indonesia’s unitary state, identify juridical constraints faced, and formulate legal reform efforts to optimize its implementation. The research method employs a normative legal approach with analysis of legislation and policy documents related to special autonomy. Research findings indicate that special autonomy implementation in the three regions has different characteristics: Aceh successfully created post-conflict political stability but faces challenges in implementing Islamic law and human rights issues; Papua receives substantial fiscal support but is constrained by weak institutional capacity and social conflicts; while DIY demonstrates a stable model due to the Sultan’s cultural legitimacy. Main constraints include overlapping authorities, regulatory inconsistencies, and weak evaluation systems. This research concludes that special autonomy requires comprehensive legal reform through regulatory harmonization, strengthened supervision, institutional restructuring, human resource capacity development, and enhanced community participation to achieve the goals of recognition, empowerment, and regional community welfare fairly and sustainably within the NKRI framework Negara Kesatuan Republik Indonesia menghadapi tantangan kompleks dalam mewujudkan keadilan dan kesejahteraan bagi seluruh rakyat yang tersebar di wilayah yang luas dengan keberagaman suku, budaya, dan kondisi geografis yang sangat beragam. Untuk mengatasi hal tersebut, pasca reformasi 1998, Indonesia menerapkan kebijakan desentralisasi asimetris melalui pemberian status otonomi khusus kepada beberapa daerah seperti Aceh, Papua, dan Daerah Istimewa Yogyakarta berdasarkan kekhususan historis, budaya, dan kondisi sosial-politik masing-masing daerah. Penelitian ini bertujuan untuk menganalisis implementasi otonomi khusus sebagai wujud desentralisasi asimetris dalam kerangka negara kesatuan Indonesia, mengidentifikasi kendala yuridis yang dihadapi, serta merumuskan upaya reformasi hukum untuk mengoptimalkan pelaksanaannya. Metode penelitian menggunakan pendekatan hukum normatif dengan analisis terhadap peraturan perundang-undangan dan dokumen kebijakan terkait otonomi khusus. Hasil penelitian menunjukkan bahwa implementasi otonomi khusus di ketiga daerah memiliki karakteristik yang berbeda: Aceh berhasil menciptakan stabilitas politik pasca-konflik namun menghadapi tantangan dalam penerapan syariat Islam dan isu HAM; Papua menerima dukungan fiskal besar tetapi terkendala lemahnya kapasitas kelembagaan dan konflik sosial; sedangkan DIY menunjukkan model yang stabil berkat legitimasi kultural Sultan. Kendala utama meliputi tumpang tindih kewenangan, ketidaksinkronan regulasi, dan lemahnya sistem evaluasi. Penelitian ini menyimpulkan bahwa otonomi khusus memerlukan reformasi hukum menyeluruh melalui harmonisasi regulasi, penguatan pengawasan, restrukturisasi kelembagaan, pengembangan kapasitas SDM, dan peningkatan partisipasi masyarakat agar dapat mencapai tujuan pengakuan, pemberdayaan, dan kesejahteraan masyarakat daerah secara adil dan berkelanjutan dalam kerangka NKRI.